Trans-boundary pollution and international migration - Kondoh Kenji (European Regional Science Association (ERSA), 2002)
Adopting the basic Ricardian static trade model, Two-country (Home and Foreign), Two-goods (Agricultural and Industrial) and One-factor (labour) model with environmental resource, we extended Copland and Taylor (1999) in three points. Firstly, we assumed pollution should be trans-boundary. Secondly, we considered the technical difference between two countries. Thirdly, we introduced international migration. We assumed that the only difference between two countries is the pollution protecting technology caused by industrial production. There will occur three different situations depending on the strength of demand on industrial good. Firstly, if industrial good is strongly preferred, the country with low technology (country L) will specialize in production of industrial good and another country (country H) will produce both goods. In this case, if trade is permitted, country L will gain while whether country H will gain or not is ambiguous. Moreover, after free trade, there occurs no international migration. Secondary, if both goods are preferred almost equally, then country H (L) will specialize agricultural (industrial) good. Whether free trade is beneficial or not for each country depends on parameters. After trade, there remains wage gap between two countries and therefore international migration from L to H will occur. Thirdly, if industrial good is weakly preferred, then country L produces both goods while country H produces agricultural good only. In this case free trade will reduce the economic welfare of country L while the effects on country H is ambiguous. After free trade, workers will migrate from L to H if permitted. In the second and third cases, migration expands the production of agricultural good but reduces that of industrial good and it will continue until comparative advantage of each country diminishes. If we consider that one of the two goods is non-tradable, there is no possibility of international trade but if international migration is permitted, workers in country L will migrate to country H, which will not end before all of inhabitants in country L quit their home country.
Keywords: 330